Optimalisasi Pemahaman Pemanasan dan Pendinginan untuk Mencegah Cedera pada Klub Olahraga - Nurhidayat, Nurhidayat; Jariono, Gatot; Warthadi, Anugrah Nur; Sistiasih, Vera Septi; Hernawan, Budi (Universitas Nusantara PGRI Kediri, 2024)
One of the goals of PKM is to avoid injury to body parts when exercising, so it is very important to do warm-up and cool-down exercises. Although warm-up activities performed gradually make the body sweat and increase its temperature, it helps the heart and blood vessels because it increases blood flow to the brain. For this reason, there needs to be training focused on